Participação do fenômeno de dependência de estado nos efeitos cognitivos de diferentes drogas com potencial de abuso - Sanday, Leandro [UNIFESP] (2011)
Drug abuse can be understood as a pathological usurpation/subversion of learning and memory mechanisms that, under physiological circumstances, modulate survival behaviors related to reward and reward-related cues. In this way, cognitive processes could reinforce the motivational impact of drug-associated stimuli. In fact, it has been suggested that the neural substrates that underlie learning and memory are central components of the classical network that ensembles drug abuse. In parallel, a great amount of evidence suggests that the retrieval of learned information requires that the animal be in a state similar to that in which the memory for this information was acquired, a phenomenon so-called state-dependency, which has been demonstrated after administration of several psychoactive drugs. In this scenario, state-dependency has been related to psycho-physiological and pathological mechanisms of drug abuse. The present work aimed to verify the role of state-dependency on the cognitive effects induced by the acute administration of ethanol, amphetamine, caffeine and midazolam. Our results suggest that the cognitive impairments induced by these drugs are critically state-dependent thereby strengthening the notion of the participation of this phenomenon on drug abuse.